2022
DOI: 10.3390/ijms232113364
|View full text |Cite
|
Sign up to set email alerts
|

The Organogermanium Compound 3-(Trihydroxygermyl) Propanoic Acid (THGP) Suppresses Inflammasome Activation Via Complexation with ATP

Abstract: Inflammasome activity is a key indicator of inflammation. The inflammasome is activated by pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), which activate the p38-NF-κB pathway and promote IL-1β transcription (signaling step 1). Next, extracellular adenosine triphosphate (ATP) activates the inflammasome (a protein complex consisting of a signal recognition protein, an adapter protein, and Caspase-1) and secretion of inflammatory cytokines such as IL-1β (signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In addition, Ge-132 has been shown to suppress the secretion of inflammatory cytokines, such as IL-6 and IL-1β, via p38-NF-κB signaling when primary mouse mammary epithelial cells are treated with LPS [37]. Furthermore, we recently discovered that THGP suppresses inflammasome activation by LPS and ATP stimulation via complexation between THGP and ATP [38]. Therefore, THGP might act as an immunomodulator, not only an M1 differentiation inducer or anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ge-132 has been shown to suppress the secretion of inflammatory cytokines, such as IL-6 and IL-1β, via p38-NF-κB signaling when primary mouse mammary epithelial cells are treated with LPS [37]. Furthermore, we recently discovered that THGP suppresses inflammasome activation by LPS and ATP stimulation via complexation between THGP and ATP [38]. Therefore, THGP might act as an immunomodulator, not only an M1 differentiation inducer or anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to assess the possible mechanisms of this physiological activity, the interaction of THGPA with biologically active compounds such as adrenaline and ATP, which have vicinal diol functional groups, has been studied in detail. The found interaction with these diols explains numerous physiological functions of Ge-132 at its low toxicity [52,105]. It was later found that in solution THGPA is able to form complexes with nucleotides or nucleosides containing also cis-diol fragment [106].…”
Section: R = Ch2ch2coohmentioning
confidence: 95%
“…Thus, THGPA is shown to inhibit melanoma cell proliferation through phagocytosis [103]. Besides, it reveals analgesic [104] and anti-inflammatory effects [105]. THGPA contains three hydroxy groups in its molecule, which can react with OHgroups of vital molecules.…”
Section: R = Ch2ch2coohmentioning
confidence: 99%
“…Inflammasome, as a member of innate immunity, is a multi-protein oligomer activated under inflammation- and immune-related challenges ( Bai et al, 2022 ; de Carvalho Ribeiro & Szabo 2022 ; Toldo et al, 2022 ). It is mainly produced in macrophages, neutrophiles, dendritic cells and other inflammatory and immune cells to contribute to the induction of inflammatory and immune responses via the recognition of pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns (DAMPs) ( Azumi et al, 2022 ; Biasizzo & Kopitar-Jerala, 2020 ; Herwald & Egesten, 2016 ). As previously reviewed by us, several kinds of inflammasomes have been reported, namely NOD-like receptor family, pyrin domain-containing (NLRP)1, NLRP2, NLRP3, NLR family caspase recruitment domain-containing protein 4 (NLRC4), and double-stranded DNA sensors absent in melanoma 2 (AIM2) ( Shao, Cao & Liu, 2018 ; Shao et al, 2015 ).…”
Section: Part I: Biological Features Of Netsmentioning
confidence: 99%